Populist leaders and political parties - Barber, N (Goethe University Frankfurt, 2019)
Populism is a particular type of constitutional pathology; a brand of groupthink in which a leader establishes a direct connection with the people and, by virtue of this connection, is able to govern outside the established constitutional processes of the state. This Article reflects on the interaction between populism and political parties. It argues that one of the roles of political parties is to act as a medium between political elites and the people; a medium that can, or should, enable the people to exercise control over this elite through their membership of parties. Populism therefore presents a threat to the proper operation of political parties, and the proper operation of political parties correspondingly threatens populism. This Article begins by reflecting on the nature of populism. It does not pretend to provide a complete account of that phenomenon, but rather aspires to identify one strand of populist rule: A particular type of connection between the leader and her people. Second, the paper reflects on the constitutional role of political parties. Whilst political parties have often been treated critically in British constitutional scholarship, it will be argued that they are essential to the success of the democratic process: Modern representative democracy cannot function in their absence. Finally, these two sections of the paper will be drawn together: One explanation for the rise of populism is the weakness of political parties, and one way of combating, or mitigating, populism is for the state, and the citizenry, to support and facilitate parties. This Article suggests a correlation between the decline of political parties and the rise of populism, but it cautiously avoids making claims of causation. It could be that the decline of political parties leads to the rise of populism, as voters who are faced with a choice of superannuated parties turn, instead, to charismatic individuals. Or it could be that the rise of populism leads to the decline of political parties, as voters develop a direct relationship with leaders and, as a result, cease to engage with each other within the context of parties. Or, perhaps, these interactions might occur together, forming a feedback loop, with the decline of parties leading to the rise of populism which, in turn, hastens party decay.